Thrombotic microangiopathy involving kidney allograft and peripheral nerves. Issue 5 (27th December 2019) - Naddaf, Elie; James B. Dyck, P.; Said, Samar; Amer, Hatem
Abstract : While thrombotic microangiopathy (TMA) can commonly affect the kidney, peripheral nerve involvement has not been reported to date. A 56‐year‐old man, recipient of a kidney allograft, reported severe headaches, tremors, and diarrhea followed by sudden‐onset right foot drop after increasing his dose of tacrolimus. He then developed acute right hand pain, numbness, and weakness. At presentation, neurological examination and electroneuromyography confirmed the presence of right worse than left, sciatic and ulnar mononeuropathies. Kidney biopsy showed evidence of a thrombotic microangiopathy. Similarly, nerve biopsy showed thrombosis of epineurial blood vessels with minimal inflammation. Herein, we demonstrated that thrombotic microangiopathy can involve the peripheral nerves, resulting in major morbidity. Distinguishing TMA from vasculitis is important because it has major treatment implications. Abstract : The authors report a 56‐year‐old man, recipient of a kidney allograft, who developed worsening kidney function and acute‐onset multiple mononeuropathies right after his tacrolimus dose was increased, with evidence of a thrombotic microangiopathy on both kidney and nerve biopsies.